2017
DOI: 10.1039/c7me00063d
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable n-type thermoelectric materials fabricated via electron doping into inkjet-printed carbon nanotubes using oxygen-abundant simple polymers

Abstract: Single-walled carbon nanotubes (SWCNTs) are important candidates for flexible and non-toxic thermoelectric (TE) energy-harvesting devices because they have large Seebeck coefficients, good flexibility, and inkjet printability onto plastic substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The authors reported that the prepared n type TE films achieved the highest power factor of 1500 µW/mK 2 with 1 wt.% PEI content. Likewise, Horike et al [93] switched a p type SWCNT into an n type by polymer doping. Thus, four different polymer solutions, including poly(vinyl chloride) (PVC) , poly(vinyl pyrrolidone) (PVP), poly(vinyl alcohol) (PVA) and poly(vinyl acetate) (PVAc) were drop casted over p type SWCNT thin films as electron donors.…”
Section: N Type Carbon Based Te Compositesmentioning
confidence: 99%
“…The authors reported that the prepared n type TE films achieved the highest power factor of 1500 µW/mK 2 with 1 wt.% PEI content. Likewise, Horike et al [93] switched a p type SWCNT into an n type by polymer doping. Thus, four different polymer solutions, including poly(vinyl chloride) (PVC) , poly(vinyl pyrrolidone) (PVP), poly(vinyl alcohol) (PVA) and poly(vinyl acetate) (PVAc) were drop casted over p type SWCNT thin films as electron donors.…”
Section: N Type Carbon Based Te Compositesmentioning
confidence: 99%
“…In the case of PVP-NOGF, the naturally high HOMO level of the polymer has been reported to induce electron donation in both graphene [18,22] and CNTs. [28] However, further study would be needed to confirm the exact charge-transfer mechanisms.…”
Section: Synthesis and Characterization Of Pba-nogfmentioning
confidence: 99%
“…PEO can provide electron carriers for polymer matrix as presented by Luo et al Similarly, diethylene glycol has been used as dopant to increase the electronic conductivity of poly(3,4‐dioxythiophene)‐polystyrene sulfonate . Oxygen‐abundant polymers, such as poly(vinyl alcohol) and poly(vinyl acetate), have been used to modify SWCNT preparing air‐stable n‐type SWCNT . Therefore, p–n transition is attributed to PEO chain segment.…”
Section: Resultsmentioning
confidence: 99%